Kesulitan guru geografi SMA dalam menyusun soal higher order thinking skills berdasarkan kurikulum 2013 - Ceres Antika Putri; Yusuf Suharto; Purwanto Purwanto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
Higher order thinking skills are realized through the implementation of HOTS questions which still have difficulties in the preparation. This study aims to determine the level of difficulty, form of difficulty, causal factors, and mapping the difficulties of geography teachers in preparing HOTS questions. The design of this study is a survey with quantitative descriptive analysis and presented in the form of graphics and maps. High school geography teachers in Malang City have difficulty implementing HOTS cognitive level indicators on the items because there is no manual for the preparation of HOTS questions specifically for geography. Based on the results of mapping teachers in public schools have lower levels of difficulty compared to teachers in private schools. Kemampuan berpikir tingkat tinggi diwujudkan melalui implementasi soal HOTS yang masih terdapat kesulitan dalam penyusunannya. Penelitian ini bertujuan mengetahui tingkat kesulitan, bentuk kesulitan, faktor penyebab, serta pemetaan kesulitan guru geografi dalam menyusun soal HOTS. Rancangan penelitian ini adalah survei dengan analisis deskriptif kuantitatif dan disajikan dalam bentuk grafis dan peta. Guru geografi SMA di Kota Malang kesulitan dalam mengimplementasikan indikator-indikator level kognitif HOTS pada butir soal karena belum adanya buku panduan penyusunan soal HOTS khusus geografi. Berdasarkan hasil pemetaan guru-guru di sekolah negeri memiliki tingkat kesulitan yang lebih rendah dibandingkan dengan guru di sekolah swasta.